Eine Analyse von zyklischen Systemen unter Unbestimmtheitsbedingungen - Kapliñski, O. (Journal of Civil Engineering and Management, 1995)
This paper presents the problem of balancing specific construction processes with cyclic configuration. The processes of assembly of forming equipment in a monolithic housing building are an example of the consideration. The rules decomposition and synthesis at the production system has been used. Three examples of the loss functions are given. The results of analysis have been compared by means of Laplace’s and Wald’s criterions. Article in German. First Published Online: 26 Jul 2012